A comparative investigation of premixed flame propagating of combustible gases-methane mixtures across an obstructed closed tube. (1st April 2021) - Li, Ruikang; Luo, Zhenmin; Cheng, Fangming; Wang, Tao; Lin, Haifei; Liu, Han
Highlights: The existence of obstacles as a radiator resulting in a special triple flame. The order of the influence of combustible gas on CH4 /air mixture is given. A crescent-shaped backwards flow field in the burned area is found. Flame brightness is closely related to flame tip speed and explosion pressure. Abstract: In this study, the premixed flame behaviour of CH4 /air mixtures (7 vol%, 9.5 vol% and 11 vol%) is investigated upon the addition of four emblematic combustible gases (0–2 vol%)—CO, H2, C2 H4, and C2 H6 . The investigation is carried out in a closed tube (L/D = 9) containing an obstacle (BR = 18%) acting as a radiator at 0.1 MPa and 25 °C. The flame structure, flame-tip speed, and flame-tip position were obtained by analysing the images captured by a high-speed camera. The explosion pressure history was recorded and analysed to study the effects of these parameters on the flame propagation process. Meanwhile, the flame brightness and flow field near the obstacle were discussed. The results indicate that the existence of obstacles deformed the generated tulip flame, resulting in a special triple flame, and the pressure history appeared stepped. The order of impact on the explosion reaction of rich conditions of the CH4 mixtures was C2 H4, C2 H6, H2, and CO; however, the order of impact on that of the stoichiometric and lean conditions of the CH4 mixtures was C2 H6, C2 H4, CO, and H2 . After the flame crossed the obstacle, a crescent-shaped backward flow field in the burned area. The brightness curve was also stepped like the pressure history when the flame crossed the obstacle, and the flame brightness started to rise rapidly at the maximum flame tip speed. This is evidence that the flame brightness was closely related to the flame-tip speed and explosion pressure.